Capitalismo e imperialismo norteamericano / Paul Sweezy : . Teoría de la política exterior norteamericana / Leo Huberman, Paul M. Sweezy - Huberman, Leo; Sweezy, Paul M. (Paul Marlor) (Documentos)
Datos tomados de la cub.